Mass Communications: From Classics to the Virtual Models - Karaperyan, Anrieta (Journal of Sociology: Bulletin of Yerevan University, 2020)
The article is devoted to the widespread use of mass communications and their virtual models, features and limitations, as well as the comparison of virtual and classical models. To study virtual communications, it is not enough to describe the corresponding processes within the framework of classical models, as well as the communication elements included in them. In order to fully describe modern communication processes, it is proposed to supplement the classical models with such elements as feedback, perception and self-presentation of the user, as well as the virtual communication space.
Keywords: Mass communication; virtual communication; virtual environment; models of communication; feedback; self-presentation; virtual as the message